PERANCANGAN KAMPANYE SOSIAL UPAYA PELINDUNGAN BAHASA DAERAH UNTUK REMAJA SEBAGAI BAGIAN MASYARAKAT URBAN DI INDONESIA - Eleanora Josephine (Wimba : Jurnal Komunikasi Visual, 2022)
It is undeniable that technological advances and globalization have brought many positive changes to various aspects of human life. However, the advent of cross-cultural phenomena and the flow of information that knows no boundaries are gradually shifting the cultivation of Indonesian culture within its society. As a country diverse both biologically and culturally, Indonesia currently acknowledges 718 native languages throughout the archipelago. However, the use of native languages within the general public has been diminishing compared to national or even international languages due to several reasons concerning the functionalities of native languages that often may not benefit the parties who use them. As a result, some native languages are in critical condition or, to a greater extent, towards extinction – Indonesia’s Badan Bahasa claimed that 11 native languages in Indonesia have become extinct. Government officials have begun to activate protection programs for native languages. Still, they have yet to reach youth audiences fully – the supposed generation to inherit them – and interest them in the subject. Therefore, to revitalize native languages, it is crucial to incorporate a social campaign that could influence the youth to participate in the protection program. The design thinking model is practiced upon defining the core problem, discovering insights of the target audience, and determining the direction until prototyping the social campaign in question. The data analysis from survey results and interviews has helped gain insights into the targeted audience. The result proves that nearly half of the survey participants do not know about the dire situation of regional languages in Indonesia and its protection program. At the same time, a part of them needs a proper platform to express their concerns. Hence, the social campaign is expected to convince a change of perspective and encourage youth’s participation in revitalizing Indonesia’s native languages.